Subjective Completion Beliefs and the Demand for Post-Secondary Education - Johannes S. Kunz; Kevin E. Staub (Institute for the Study of Labor (IZA), 2016)
The outcome of pursuing an upper or post-secondary education degree is uncertain. A student might not complete a chosen degree for a number of reasons, such as insufficient academic preparation or financial constraints. Thus, when considering whether to invest in post-secondary education, students must factor their probability of completing the degree into their decision. We study the role of this uncertainty in education choices using representative survey data from Germany. Students' subjective beliefs about the probability of completing a post-secondary education were elicited prior to them finishing their secondary education. We relate these subjective completion probabilities to students' subsequent education choices and outcomes. We find that these early beliefs are predictive of intentions to invest in education, actual subsequent investments in education, and degree completion. A structural choice model of sequential investment further reveals that the association between completion beliefs and investment choices is strongest for students with low academic skills and low preferences for post-secondary education.
Keywords: I21; I26; J24; 330; subjective beliefs; subjective probabilities; completion uncertainty; post-secondary education; human capital investment